(untitled) (Web of Teachers: Inderscience Research, 2025)
The integration of interactive methods in teaching grammar to young learners has revolutionized traditional language instruction by fostering a more engaging and learner-centered environment. This paper explores the methodological characteristics of interactive approaches, emphasizing their role in enhancing grammar acquisition among primary and secondary school students. The study highlights key principles such as collaboration, communication, and real-world relevance, which form the foundation of interactive grammar teaching. Various techniques—including games, group work, role-playing, and technology-assisted tasks—are examined for their pedagogical value. Through theoretical analysis and practical application, the research demonstrates how interactive methods not only improve grammatical competence but also boost learner motivation and participation. The findings affirm that interactive teaching methods align well with the cognitive and emotional development of young learners, leading to more effective and meaningful grammar instruction.